Top-quark pair production as a probe of light top-philic scalars and anomalous Higgs interactions - Fabio Maltoni; Davide Pagani; Simone Tentori (Journal of High Energy Physics)
Abstract We compute the effects due to the virtual exchange (or the soft emission) of a scalar particle with generic couplings to the top quark in t t ¯ $$ t\overline{t} $$ pair production at the LHC. We apply the results to two cases of interest, extending and completing previous studies. First, we consider the indirect search for light (m S < 2m t ) top-philic scalars with CP-even and/or CP-odd interactions. Second, we investigate how to set constraints on anomalous Yukawa couplings of the Higgs boson to the top quark. Our results show that the current precision of experimental data together with the accuracy of the SM predictions make such indirect determinations a powerful probe for new physics.